100 år med arkæologiske undersøgelser i Slesvig-Holsten–et kig tilbage - Ickerodt, Ulf (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
From the perspective of research history, it is important to find the beginning of developments and practices. there are always precursors of structures, approaches, methods and practices. For today`s Schleswig-Holstein state archaeology, the date of 1 January 1923 can justifiably be cited. This date marks the creation of a structure that remains the basis for archaeological law and conservation tasks. !e aim was and is to record all archaeological sites and finds. Even though the introduction was already »up in the air« at the time, the initial financing of this task, then its transformation into a provincial office, archaeological state authority validated by the first state monument protection law in Germany. In this paper, the history of state archaeology will be presented from various perspectives in its methodological and systematic context.